2003
DOI: 10.1093/ndt/gfg064
|View full text |Cite
|
Sign up to set email alerts
|

Iron-mobilizing properties of the gadolinium-DTPA complex: clinical and experimental observations

Abstract: The combination of iron overload and lack of adequate clearance of Gd chelates may cause massive liberation of iron with dangerous elevation of free serum iron. It is highly recommended that after Gd contrast study, end-stage renal disease patients with probable iron overload should undergo prompt and intensive haemodialysis for prevention of this serious complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…A similar phenomenon has been implicated in iron metabolism abnormalities after exposure to gadolinium-DTPA containing contrast. 15 It is widely recognized that DTPA-BMA, a component of the chelate in gadodiamide, may impair calcium measurements in recently exposed patients, particularly in those with renal failure. 16 Similarly, alterations in zinc and copper homeostasis have followed administration of gadolinium-containing contrast agents, presumably because of transmetallation of gadoliniumchelate complexes.…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon has been implicated in iron metabolism abnormalities after exposure to gadolinium-DTPA containing contrast. 15 It is widely recognized that DTPA-BMA, a component of the chelate in gadodiamide, may impair calcium measurements in recently exposed patients, particularly in those with renal failure. 16 Similarly, alterations in zinc and copper homeostasis have followed administration of gadolinium-containing contrast agents, presumably because of transmetallation of gadoliniumchelate complexes.…”
Section: Discussionmentioning
confidence: 99%
“…No gadolinium was identified in a tissue sample from any patient without NSF. Other metals found in the tissues of NSF patients included large deposits of iron, copper, and zinc (23,25,52), and this in itself may betoken transmetallation. Of particular interest is their determination that in all four cases the gadolinium was intracellular.…”
Section: Stability In Practicementioning
confidence: 99%
“…If a patient answers in the negative to a series of questions concerning: a history of renal problems, renal surgery, hypertension, congestive cardiac failure, diabetes, and taking of other nephrotoxic drugs (e.g., diuretics, nonsteroidal antiinflammatory drugs [NSAIDs], aminoglycosides, amphotericin, or cyclosporin A), it seems unlikely, if not impossible, that a patient with undetected ESRF would attend unheralded as an outpatient and pass such a screening. Importantly, this is essentially the approach taken by the MHRA in the United Kingdom in its own latest guidance (52). Some may choose to take a more cautious line but may find administration of MR services more complicated as a result.…”
Section: Managing the Situationmentioning
confidence: 99%
“…However the Gd(III) aqua ion itself cannot be used because it forms insoluble phosphate, carbonate, and/or hydroxide complexes in blood at pH 7.4. Moreover it has been shown that Gd(III) is toxic to human cells in vitro [6–8] and to rats [9] in vivo likely due to the inhibition of transmembrane currents through Ca(II) channels [1011] or by forming inorganic insoluble salt aggregates with anions such phosphates [1213]. …”
Section: Introductionmentioning
confidence: 99%